Sistemática para mapear áreas do conhecimento da ciência brasileira : o caso da nanotecnologia - Brito, Aline Grasiele Cardoso de (Universidade Federal de São Carlos, 2016)
In recent years the social studies of science have revealed a special interest in the extraction of knowledge in databases, which enables the treatment and analysis of sets of data available on the scientific and technological production of researchers, institutions and countries. The objective of this research was to develop and apply a systematics for the collection, treatment and analysis of information about areas of scientific knowledge in Brazil, using essentially open access data and free tools. The method was a case study, the unit case was the priority area nanotechnology and the source of information comprised the bases: Lattes Curriculum Base; Directory of Search Groups; Brazilian Digital Library of Theses and Dissertations; And the Espacenet of the European Patent Office. The results achieved were 1) the creation and presentation of a systematic for the collection, treatment and analysis of information 2) indicators for the treated area. It is concluded that the Information in Science and Technology, with open access, allow a democratic generation of knowledge in this context. The sources of information and the set of tools made possible the elaboration of indicators capable of elucidating multiple dimensions of scientific and technological production - of researchers and research groups - in addition to teaching and research in postgraduate studies. The indicators obtained and their application reinforce the objective of the data mining process, in the sense of transforming data into information to be used in the decision-making process of organizations that are dedicated to the preservation and innovation of knowledge.
Keywords: Indicadores em Ciência e Tecnologia; Acesso Aberto; Currículos Lattes; Grupos de Pesquisa; Espacenet; BDTD; Nanotecnologia; Mineração de dados; Indicators of Science and Technology; Data mining; Open Access; Lattes resumes; Research Groups; Nanotechnology; CIENCIAS HUMANAS::EDUCACAO